2022
DOI: 10.1002/etc.5451
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Accumulation of Ionizable Pharmaceuticals and Personal Care Products in Aquatic and Terrestrial Organisms

Abstract: The extent to which chemicals bioaccumulate in aquatic and terrestrial organisms represents a fundamental consideration for chemicals management efforts intended to protect public health and the environment from pollution and waste. Many chemicals, including most pharmaceuticals and personal care products (PPCPs), are ionizable across environmentally relevant pH gradients, which can affect their fate in aquatic and terrestrial systems. Existing mathematical models describe the accumulation of neutral organic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 147 publications
0
25
0
Order By: Relevance
“…For example, we previously reported bioaccumulation of the ionizable base diphenhydramine in adult Pimephales promelas (fathead minnows) to be under predicted by log D ow (Nichols et al, 2015), an observation similar to the present study with sertraline. In the present study, the human pharmacokinetic proportionality factor, apparent volume of distribution (V D ; Table 1), appears particularly useful for advancing bioaccumulation modeling of ionizable contaminants because it describes internal distribution regardless of the basis for chemical behavior (Carter et al, 2023). For example, Zhang et al (2022) recently identified that V D was a better predictor of kinetic‐based BCF values for ionizable pharmaceuticals in zebrafish ( Danio rerio ) than log D ow or log D liposome‐water .…”
Section: Resultsmentioning
confidence: 99%
“…For example, we previously reported bioaccumulation of the ionizable base diphenhydramine in adult Pimephales promelas (fathead minnows) to be under predicted by log D ow (Nichols et al, 2015), an observation similar to the present study with sertraline. In the present study, the human pharmacokinetic proportionality factor, apparent volume of distribution (V D ; Table 1), appears particularly useful for advancing bioaccumulation modeling of ionizable contaminants because it describes internal distribution regardless of the basis for chemical behavior (Carter et al, 2023). For example, Zhang et al (2022) recently identified that V D was a better predictor of kinetic‐based BCF values for ionizable pharmaceuticals in zebrafish ( Danio rerio ) than log D ow or log D liposome‐water .…”
Section: Resultsmentioning
confidence: 99%
“…It was recommended to standardize plant uptake test systems, and to record influential physiological and environmental parameters (Doucette et al, 2018), and it was found that plant-specific parameters can have as much influence on chemical uptake as physicochemical parameters (Trapp, 2015). Carter et al (2022) addressed current obstacles in the model development for the prediction of accumulation of PPCPs in aquatic and terrestrial organisms, and concluded that further progress is hampered by a lack of mechanistic insights, mainly for ions. The authors stimulated research into partitioning and sorption behavior, membrane permeabilities, salts and complexes, and on biotransformation and elimination processes of ions.…”
Section: Limitations and Shortcomingsmentioning
confidence: 99%
“…Among the most pressing research questions for PPCPs is “How can the uptake of ionizable PPCPs into aquatic and terrestrial organisms and through food chains be predicted?” (Boxall et al, 2012). It was concluded that “improved models should be developed for estimating uptake of ionizable PPCPs into organisms and through food chains,” and major obstacles and key research questions to derive such models were addressed in Carter et al (2022).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, PFAS have been found to bioaccumulate in tissues of aquatic organisms, wildlife, and birds, and this accumulation is dissimilar to legacy contaminants such as polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs; Giesy & Kannan, 2001) largely because PFAS have been found to bind to proteins and other biopolymers (Bischel et al, 2010; Liang et al, 2022; MacManus‐Spencer et al, 2009; Wen et al, 2019). Similar to other ionizable contaminants that fall outside the applicability domain of predictive bioaccumulation models for nonionizable organics (Carter et al, 2022; Nichols et al, 2015), kinetic information to model bioaccumulation of PFAS in freshwater ecosystems is needed (Bertin et al, 2016; Prosser et al, 2016). In addition, accumulation dynamics of PFAS by aquatic life may differ based on the organisms’ feeding and behavior (Lewis et al, 2022).…”
Section: Introductionmentioning
confidence: 99%